Quaking promotes monocyte differentiation into pro-atherogenic macrophages by controlling pre-mRNA splicing and gene expression - Ruben G. de Bruin (Nature Portfolio, 2016)
Post-transcriptional control of RNA is important in health and disease. Here, the authors show that the RNA-binding protein Quaking guides pre-mRNA splicing and transcript abundance during monocyte to macrophage differentiation, and that Quaking depletion impairs pro-atherogenic foam cell formation.